2007
DOI: 10.1089/jop.2006.0137
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Pharmacodynamics, Pharmacokinetics, and Safety of BOL-303224-A, a Novel Fluoroquinolone Antimicrobial Agent for Topical Ophthalmic Use

Abstract: BOL-303224-A is a novel fluoroquinolone that has never been used systemically and that possesses structural modifications intended to improve its potency compared to other fluoroquinolones. This investigation was conducted to evaluate the nonclinical pharmacokinetics, safety, and pharmacodynamics of BOL-303224-A. BOL-303224-A displayed activity in in vitro antimicrobial efficacy studies and also demonstrated efficacy in an in vivo murine infection model. BOL-303224-A demonstrated excellent ocular pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 15 publications
(18 reference statements)
1
38
0
1
Order By: Relevance
“…15 The penetration of besifl oxacin into cornea was evaluated using male Dutch-belted rabbits in the present investigation. Other study design considerations were consistent with the conduct of the previous reported study.…”
Section: Nonclinical Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The penetration of besifl oxacin into cornea was evaluated using male Dutch-belted rabbits in the present investigation. Other study design considerations were consistent with the conduct of the previous reported study.…”
Section: Nonclinical Pharmacokineticsmentioning
confidence: 99%
“…Other study design considerations were consistent with the conduct of the previous reported study. 15 Briefl y, each rabbit received a 50-μL instillation of besifl oxacin ophthalmic suspension (0.6%) into the conjunctival sac of each eye as a single bolus dose. At predetermined time intervals after dosing, rabbits (n = 4 per collection time) were euthanized and the eyes enucleated, frozen, and dissected, with tissues collected separately for each eye.…”
Section: Nonclinical Pharmacokineticsmentioning
confidence: 99%
“…30 Further, the C-8 chlorine substitution is thought to improve activity against organisms with DNA gyrase mutations. 31 Figure 2 depicts the chemical structures of several fluoroquinolones. In addition to point mutations in the bacterial genes encoding DNA gyrase and topoisomerase IV, efflux pumps may also mediate fluoroquinolone resistance.…”
Section: Besifloxacinmentioning
confidence: 99%
“…1) is a novel, chiral synthetic fluoroquinolone being developed by Bausch & Lomb for the topical treatment of ophthalmic infections. Structurally, besifloxacin has an N-1 cyclopropyl group, which provides broad-spectrum activity against aerobic bacteria [7]. The main mechanism of action of besifloxacin is the inhibition of both DNA gyrase and topoisomerase-IV enzymes that are involved in coiling and uncoiling of bacterial DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of action of besifloxacin is the inhibition of both DNA gyrase and topoisomerase-IV enzymes that are involved in coiling and uncoiling of bacterial DNA. This activity is enhanced by a C-8 chloride substituent in besifloxacin, which also exhibits improved activity against gram-positive bacteria relative to older fluoroquinolones while still retaining potent efficacy against anaerobic bacteria [7].…”
Section: Introductionmentioning
confidence: 99%